2022
DOI: 10.4018/ijssci.310942
|View full text |Cite
|
Sign up to set email alerts
|

A Privacy-Preserving Authentic Healthcare Monitoring System Using Blockchain

Abstract: Integrating the internet of things (IoT) and healthcare monitoring systems is one of the most dynamic innovations in the research area. Since the tremendous number of IoT devices in smart healthcare systems is increasing exponentially, privacy and security issues related to the patient's data are significant concerns. The authors propose an access control for a healthcare monitoring system using blockchain-based smart contracts. They created four smart contract forms for user registration, authentication, acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Similarly, Raj et al. have suggested a customized access control system specifically designed for monitoring systems in the Healthcare domain [14]. This validates the effectiveness of the technology and its appropriateness for these fields.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similarly, Raj et al. have suggested a customized access control system specifically designed for monitoring systems in the Healthcare domain [14]. This validates the effectiveness of the technology and its appropriateness for these fields.…”
Section: Introductionmentioning
confidence: 72%
“…As exemplified, Umran et al have utilized the characteristics of blockchain to address the privacy and security needs related to data exchange in the field of Industrial Internet of Things (IIoTs) [13]. Similarly, Raj et al have suggested a customized access control system specifically designed for monitoring systems in the Healthcare domain [14]. This validates the effectiveness of the technology and its appropriateness for these fields.…”
Section: Introductionmentioning
confidence: 99%
“…This allows data to be tracked securely and transparently. To decrease installation and implementation delay as well as mean reaction latency in the real-time smart healthcare system, Raj et al developed blockchain-based identity management for a health surveillance system to decrease installation and implementation delay and mean reaction latency in the real-time smart healthcare system [23]. Using a blockchain network, Gupta et al suggested a very effective attribute-based searchable encryption strategy for cloud-based cyber-physical medical systems [24].…”
Section: Literature Surveymentioning
confidence: 99%
“…It can help improve efficiency, reduce costs, enhance security and protect privacy in these areas. Raj et al [1] proposed an access control for a healthcare monitoring system using blockchain-based smart contracts. The proposed method can effectively improve the privacy and security of patient data.…”
Section: Introductionmentioning
confidence: 99%